1996
DOI: 10.1089/clm.1996.14.175
|View full text |Cite
|
Sign up to set email alerts
|

In VitroSynthesis of Prostaglandin E2by Synovial Tissue after Helium–Neon Laser Radiation in Rheumatoid Arthritis

Abstract: This paper reports the effect of helium-neon laser radiation (power of 5 mW and 632.8 nm wave length) on the synthesis of PGE2 in vitro in synovial tissue of biopsy samples of knee joints in patients with chronic rheumatoid arthritis stages II or III. Twelve patients were studied. Each patient received 15 applications of He-Ne laser. Eleven points for He-Ne laser applications were selected in one of the affected knees. The energy density used was 8 J/cm2 per application point. The He-Ne laser therapy reduced t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
4

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 18 publications
1
5
0
4
Order By: Relevance
“…8,9 Additionally, it has been demonstrated that He-Ne laser decreases the PGE 2 in vitro synthesis in patients with osteoarthritis and with rheumatoid arthritis of the knee. 10,11 Our results have coincided with those of other authors. [12][13][14] The objective of this work was to assess the anti-inflammatory capacity of the He-Ne laser, determined by plasmatic fibrinogen levels and the anatomopathological study of arthropathy induced by urate crystals in rats.…”
Section: Introductionsupporting
confidence: 92%
“…8,9 Additionally, it has been demonstrated that He-Ne laser decreases the PGE 2 in vitro synthesis in patients with osteoarthritis and with rheumatoid arthritis of the knee. 10,11 Our results have coincided with those of other authors. [12][13][14] The objective of this work was to assess the anti-inflammatory capacity of the He-Ne laser, determined by plasmatic fibrinogen levels and the anatomopathological study of arthropathy induced by urate crystals in rats.…”
Section: Introductionsupporting
confidence: 92%
“…Este efeito pode ser explicado, segundo Borges et al (8) , devido o relaxamento muscular e mecanismos opióides. De acordo com Barberis et al (9) e Sakurai, Yamaguchi e Abiko (10) , o efeito analgésico pode ser obtido pela interrupção da conversão do ácido aracdônico em prostaglandinas, além de promover a reabsorção de exsudatos inflamatórios, favorecendo desta forma, a eliminação de substâncias algogênicas, como bradicinina, histamina e acetilcolina, conduzindo à diminuição da inflamação e da dor.…”
Section: Artigo Originalunclassified
“…[10][11][12][13][14] Evidence indicates that phototherapy promotes local blood flow, stimulates the proliferation of cells, including epithelial and endothelial cells, keratinocytes, macrophages, lymphocytes, and fibroblasts, and increases collagen synthesis as well. [15][16] Others have shown that phototherapy with lasers, LEDs, or superluminous diodes (SLDs) accelerates inflammation, 17 promotes fibroblast proliferation, [18][19] increases chondroplasia 20 and collagen synthesis, 15,[21][22] stimulates bone repair and remodeling, [23][24] increases the vascularization of skin wounds, 25 and accelerates tissue repair in a variety of experimental models. [26][27][28][29] However, treatment parameters, such as duration of treatment, irradiance, fluence, and frequency of treatment, differ significantly from one study to another, creating mixed results and skepticism about the clinical value of phototherapy.…”
Section: Introductionmentioning
confidence: 99%